2001
DOI: 10.1186/1471-2458-1-10
|View full text |Cite
|
Sign up to set email alerts
|

Independent predictors of breastfeeding intention in a disadvantaged population of pregnant women

Abstract: Background: Breastfeeding rates in Scotland are very low, particularly in the more disadvantaged areas. Despite a number of interventions to promote breastfeeding very few women actually intend to breastfeed their baby. The aim of this study was to identify personal and social factors independently associated with intention to breastfeed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
41
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 16 publications
6
41
1
3
Order By: Relevance
“…Previous breastfeeding experience and maternal age were independent significant predictors for breastfeeding intention and feeding choice in a similar study. 24 Furthermore, Trussel et al 25 found that children of women with higher parity tended to breastfeed the longest; those with seven or more children were twice as likely to breastfed their children as women with firstborn children.…”
Section: Discussionmentioning
confidence: 98%
“…Previous breastfeeding experience and maternal age were independent significant predictors for breastfeeding intention and feeding choice in a similar study. 24 Furthermore, Trussel et al 25 found that children of women with higher parity tended to breastfeed the longest; those with seven or more children were twice as likely to breastfed their children as women with firstborn children.…”
Section: Discussionmentioning
confidence: 98%
“…Many studies have documented there are various factors associated with breastfeeding intention (Kavanagh, Lou, Nicklas, Habibi, & Murphy, 2012;McLnnes, Love, & Stone, 2001;Mitra et al, 2004;Persad & Mensinger, 2008). These factors include maternal age, education status, household income, parity, marital status, being breastfed before, mother's knowledge on the benefits of breastfeeding, mother's attitude towards breastfeeding and social support network received by mothers.…”
Section: Introductionmentioning
confidence: 99%
“…In this study breastfeeding intention was defined as the degree of confidence about practising optimal breastfeeding behaviour. Intention to breastfeed is closely related to early initiation to breastfeed and could also be a predictor of longer duration of breastfeeding (Tarrant, Younger, Sheridan-Pereira, White, & Kearney, 2010b).Many studies have documented there are various factors associated with breastfeeding intention (Kavanagh, Lou, Nicklas, Habibi, & Murphy, 2012;McLnnes, Love, & Stone, 2001;Mitra et al, 2004;Persad & Mensinger, 2008 Hamid, S. B., et.al./ 5 th AicQoL2017Bangkok, 25-27 February 2017 / E-BPJ, 2(5), March 2017 162 education status, household income, parity, marital status, being breastfed before, mother's knowledge on the benefits of breastfeeding, mother's attitude towards breastfeeding and social support network received by mothers. Interestingly, various studies have suggested that higher body mass index (BMI) was associated with adverse breastfeeding outcomes.…”
mentioning
confidence: 99%
“…Em relação à paridade, quanto maior o número de filhos tidos, maior a experiência materna, e sua segurança para lidar com seu recém-nascido e iniciar o aleitamento materno. Um estudo escocês já havia indicado, utilizando análise multivariada, que a paridade é um fator independente que prediz a intenção de amamentar 21 .…”
Section: Discussionunclassified